The Structural Creation of Virtual Power in a Large Network - Dr. Douglas K. PETERSON,; Dr. XING YuanYuan, (Journal of Management Research, 2024)
Our conventional wisdom indicates that because of their spread-out nature, performance networks for large projects are bound to experience perfect power diffusion where no one player is likely to gain hegemony over others. We might be wrong about that. It is possible that oligarchic network positioning and influence may emerge (Ansell, Bicher, Zhou, 2016) as political considerations and dominate the more traditional bureaucratic ones. These are applicable for decisions that involve an allocation of resources, adoption of technology, design of control systems, and methods of project appraisal (among others). While considerations for these seem to be dedicated to the limited set, there is a large shortage of work on the application of power in the larger context of networks and very large initiatives (VLI) that may be found in customs, trade, economic, and political unions. This can also be found in any political integration or economic integration projects, for example in the Belt and Road Initiative (BRI). The contention is that exchanges of power in formal regulated structures may be predictable, it is the informal and unregulated condition that influence performance of integration. This paper focuses on the structures for minority control and suggests these strategies to influence a network come from the influence of nodes and edges of the network, and not from top down control.